PARTISIPASI MASYARAKAT DESA BELANTING DALAM MELAKSANAKAN MUSYAWARAH PERENCANAAN PEMBANGUNAN DESA PADA PENYUSUNAN RENCANA KERJA PEMERINTAHAN DESA - ASASANDI, I GUTI NGURAH ARYAWAN; AFZAL, MUHAMMAD (Universitas Mahasaraswati Mataram, 2019)
This study aims to determine the level of village community participation in village development planning meetings to establish village government work plans (RKPDes). Belanting village is chosen using the Perposive Sampling method, with the research method using Descriptive Research. The research data collection technique uses observation techniques. From the results concluded: (1) The level of participation of the community attendance is high, (2) The constraints faced by the community when facing the development planning meeting are the letter of invitation in the village planning meeting.